2002
DOI: 10.1034/j.1600-0765.2002.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Do interleukin‐1 polymorphisms predict the development of jreiodontitis or the success of dental implants?

Abstract: Factors which increase the risk of severe adult periodontitis (AP) may also contribute to the success of dental implants. To determine which cytokines may be relevant, levels of interleukin-1alpha (IL-1alpha), interleukin-1beta (IL-1beta), interleukin-1 receptor antagonist (IL-1ra), interleukin-6 (IL-6) and interferon-gamma (IFN-gamma) mRNA were quantitated in gingival tissue from periodontitis patients and healthy controls. Periodontitis significantly increased levels of IL-1alpha, IL-1beta, IL-6 and IFN-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
94
5
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 10 publications
13
94
5
2
Order By: Relevance
“…No significant difference was found between the groups with regard to the presence of IL-1 gene polymorphisms. This result is in line with the report by Rogers et al (18) whose findings indicated no difference among groups with chronic PD, early-onset periodontitis, and no PD in the presence of IL-1A (+4845) polymorphism or positive genotype. These authors did not detect any correlation between IL-1 polymorphisms and susceptibility to implant loss.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…No significant difference was found between the groups with regard to the presence of IL-1 gene polymorphisms. This result is in line with the report by Rogers et al (18) whose findings indicated no difference among groups with chronic PD, early-onset periodontitis, and no PD in the presence of IL-1A (+4845) polymorphism or positive genotype. These authors did not detect any correlation between IL-1 polymorphisms and susceptibility to implant loss.…”
Section: Discussionsupporting
confidence: 83%
“…However, other authors found no such correlation (18)(19)(20), thus the issue remains controversial. The aim of the present study was to examine the association between IL-1β in GCF and PD activity and to investigate the presence of IL-1 gene polymorphisms and their possible relationship with the disease, in a Spanish population.…”
Section: Introductionmentioning
confidence: 74%
“…IL-1α is mainly produced by keratinocytes of the junctional or pocket epithelium, and is a mediator of local inflammation, regulating intracellular events (Dinarello, 2002). In the current study, the IL-1α rs17561 polymorphism showed a strong association with periodontitis (Rogers et al, 2002;Wagner et al, 2007;López et al, 2009). However, several other authors have been unable to demonstrate any such relationship (Anusaksathien et al, 2003;Sakellari et al, 2003;Brett et al, 2005;Kobayashi et al, 2007;Ferreira Jr. et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Otro estudio realizado por McDevitt y col. (23) con no fumadores o ex fumadores con una historia de < 5 paquetes/año, investigaron la presencia de polimorfismos en otro conjunto de genes, IL-1α (+4845) e IL-1β (+3954 s Relación del genotipo positivo con la prevalencia de la enfermedad periodontal. Rogers y col. (27) no encontraron diferencias significativas en cuanto al polimorfismo en el gen IL-1A en la posición +4845 o a ser genotipo positivo entre un grupo con enfermedad peridontal crónica, otro con periodontitis rápi-damente progresiva y un tercer grupo de pacientes sanos. Por otro lado, también observaron que la posesión de polimorfismos en los genes de la IL-1 no aumentaba la susceptibilidad en la pérdida de implantes.…”
Section: Aceptado Para Publicaciónunclassified